Evangelicalism and Masculinity Faith and Gender in El Salvador. - Santos, Jose Leonardo (Lanham : Lexington Books, 2012)
Evangelicalism makes use of gendered stories that appeal to cosmic justifications for Christian manhood and womanhood. In a poverty-stricken, violent, unstable environment, many Salvadoran men reject their own masculinity in favor of this new, spiritually transformed ideal.
Table of Contents; Preface; 1 Introduction; 2 Religion and Gender; 3 The Evangelical Worldview Story; 4 Evangelical Masculinity; 5 Catholic and Evangelical Worlds; 6 Evangelical Narrative; Bibliography; Index
Description based upon print version of record.
Keywords: Evangelistic work -- El Salvador -- History; Men (Christian theology).; Sex role -- Religious aspects -- Christianity; Evangelistic work -- El Salvador -- History; Men (Christian theology); Sex role -- Religious aspects -- Christianity; RELIGION / Christianity / History; Electronic books